Safety, Tolerability, and Dose Proportionality of a Novel Transdermal Fentanyl Matrix Patch and Bioequivalence With a Matrix Fentanyl Patch: Two Phase 1 Single‐Center Open‐Label, Randomized Crossover Studies in Healthy Japanese Volunteers. Issue 3 (3rd August 2020) - Lorch, Ulrike; Pierscionek, Tomasz; Freier, Anne; Spencer, Christopher S.; Täubel, Jörg
Abstract: Two open‐label, single‐dose, randomized crossover studies were conducted in healthy Japanesemen to (1) assess dose proportionality of 5 doses (1.38, 2.75, 5.5, 8.25, and 11.0 mg) of Lafenta, a novel matrix‐type transdermal fentanyl patch with a rate‐controlling membrane; and (2) compare patch bioequivalence (11.0 mg) with a commercially available reference patch (Durotep MT Patch [16.8 mg]). Pharmacokinetics, adhesion performance, residual fentanyl, and safety parameters were assessed. Increases in mean AUC0‐t and Cmax after application of the test patch were dose proportional. The test patch (11.0 mg) was bioequivalent to the 16.8‐mg reference patch in terms of mean AUC0‐inf, AUC0‐t, and Cmax . Residual fentanyl levels 72 hours postapplication were lower in the test than in the reference patch. Differences in adhesion performance between the test and the reference patch did not affect delivery efficacy and reliability of the novel matrix patch. Safety findings were in line with previous experiences with fentanyl. Both studies showed low variation in fentanyl exposure and delivery via the test patch. The test patch provided equivalent fentanyl exposure at a lower dose than the reference patch formulation with lower variability and the potential to lower medicinal waste.